The Analysis of Social Deixis Used on Instagram Comments in The Royal Family Instagram Account - Luthfia Nurul Hanifa; Eesya Hasna Azkiya; Vina Novitasari; Nisrina Zakia Inayah; Rima Nadila Adiningsih; Malikatul Laila (English Teaching and Linguistics Journal (ETLiJ), 2023)
Deixis is one of the branches of pragmatics. Deixis is contextual information that refers to a certain place, time, or object. In this study, the researcher is focused on analyzing social deixis in the comments on the royal family's Instagram account. Social deixis is related to familiarity and social status. Social deixis can also be defined as deixis which does not only refer to certain referent conditions but also it contains connotations that represent certain social classes. The type of social deixis is divided into two namely relational and absolute social deixis. The aim of this study is to classify and identify the kinds of social deixis in the comments of the royal family's Instagram account. The type of this study was descriptive qualitative because the data is described in sentence form. The data used in this study were taken from the social deixis in the royal family's Instagram account.